SUPPLY CHAIN MANAGEMENT OF CIGARETTE INDUSTRY IN PT DJARUM AND GUDANG GARAM INDONESIA - Elvi Andry; Santi Dwi Aviantari; Felicia Mulia; Nadia Azizah Yasmin; Antyo Pracoyo (Swakarya: Jurnal Penelitian Sosial dan Pengabdian Masyarakat, 2023)
PT Djarum and PT Gudang Garam are two of the major companies that dominate the industry. Both companies are known for their highly recognized cigarette brands both nationally and internationally. This research aims to find out the supply chain management of PT Djarum and Gudang Garam and find out the solutions to the challenges of the differences between the two companies. The results of this study indicate that: PT Djarum's supply chain management begins with a careful selection of raw materials combined between art and science. There is a secret ingredient in every production where Djarum continues to produce classic cigarette products manually. Djarum is supported by advanced laboratory technology. new. In addition to developing kretek aroma, R&D insights are also applied to the manufacturing and production side. In contrast to Djarum, Gudang Garam's supply chain management is based on the company's founding philosophy, providing a solid foundation for best practices in good corporate governance. Supply chain challenge solutions, have differences, the comparison is seen from: 1) Size and Production Capacity, Gudang Garam has a larger production capacity than Djarum with a market capitalization value of US$3.12 billion or around 47.72 trillion; 2) Brand Portfolio, both brands have high popularity in Indonesia and have different market segments; 3) Distribution, both companies have warehouses, distribution centers, and cooperation with transportation providers to ensure efficient and timely products; 4) CSR and Environment, both have a commitment to social responsibility. CSR and Environment, both have a commitment to sustainable social and environmental responsibility. Both have community development programs, education, and health initiatives